A new surgical approach to ventricular septal defect with aortic regurgitation - Kumar, Ansul; Bhattacharya, Shubhadev; Jhajhria, Narender Singh; Gupta, V. K. (International Surgery Journal, 2016)
A 9 years old male presented with dyspnea on exertion for 2 years, pan-systolic murmur with wide pulse pressure. 2D echocardiography revealed sub aortic ventricular septal defect (VSD) with sub aortic membrane and severe aortic regurgitation (AR). Aortic valve was tricuspid with prolapsed and bulky right coronary cusp (RCC) (Figure 1). There was enlarged right coronary sinus with downward displacement of hinge from annulus. Intra-operatively trans esophageal echocardiography (TEE) revealed severe AR (Figure 2).